The Transformation of Romanian Internal Public Audit between 2006 and 2020 - Octavian Moldovan; Felicia Cornelia Macarie (Transylvanian Review of Administrative Sciences, 2022)
The article analyzes how internal public audit (IPA) transformed in Romania between 2006 and 2020, in order to explore: (a) the degree in which central and local public institutions organized their IPA activities as a specialized department or in an associative structure; (b) how did the human resources allocated to IPA activities transformed in this period (focusing on employment, the ability to cover the needs of public organizations and the educational/ professional specialization of internal auditors), and (c) how IPA missions changed over time. The empirical research consists of a detailed analysis of official annual reports published by the Central Harmonization Unit for Internal Public Audit, thus ensuring the reliability of the analysis. Our main results indicate the existence of multiple differences between central and local public organizations, regarding their degree/level of IPA activities organization (especially before 2013) and the number of organizations each internal public auditor was tasked to audit (ranging from 1 at the central level to almost 8 at the local level). Unfortunately, the understaffing of IPA departments/ bureaus is not conducive to an accurate identification and assessment of potential organizational weaknesses and risks, thus potentially hindering the performance of both central and local public institutions